Pemanfaatan WhatsApp Group sebagai Media Pembelajaran dalam Pembuatan Aksesoris Bros - Henki Bayu Seta; Theresiawati Theresiawati; Jayanta Jayanta; Nurhafifah Matondang; Sarika Afrizal (Jurnal Pengabdian kepada Masyarakat Bidang Ilmu Komputer, 2025)
Community service activities aim to improve the skills and creativity of the community at the Al Mukhlisin Tajur Halang mosque, Bogor. Training in making brooch accessories uses WhatsApp Group as a learning medium. The method used in this activity is a practical approach by providing video tutorial materials on making accessories in this case making chin brooches which are shared via WhatsApp Group. In addition, WhatsApp Group is used as an interactive discussion medium, a guide to marketing their products digitally and a question and answer session. Community service activities went smoothly and received a positive response. The results of the service show that WhatsApp Group can be used as an effective learning tool and participants can easily understand and master the techniques of making brooch accessories. This program has succeeded in increasing the creativity of participants, providing additional knowledge about product marketing using easily accessible technology, and can open up new opportunities to increase income through the sale of brooch accessories and build an entrepreneurial spirit among the Tajur Halang community.